New and Extended Results On Fourth-Order Differential Subordination for Univalent Analytic Functions - Waggas Galib Atshan; Ali Hussein Battor; Abeer Farhan Abaas; Georgia Irina Oros (Al-Qadisiyah Journal of Pure Science, 2020)
In this paper, we introduce new concept that is fourth-order differential subordination and superordination associated with linear operator for univalent analytic functions in open unit disk. Here, we extended some lemmas. Also  some interesting new results are obtained.